A multi-method study of a Chalcolithic Kiln in the Bora Plain (Iraqi Kurdistan): the evidence from excavation, micromorphological and pyrotechnological analyses - Squitieri, Andrea; Amicone, Silvia; Dinckal, Ada; Altaweel, Mark; Gur-Arieh, Shira; Rohde, Jens; Herr, Jean-Jacques; Pietsch, Sophie; Miller, Christopher (Open archaeology, 2022)
Pyrotechnology has always been a core topic in the archaeological debate concerning phases of deep cultural transformations, such as the Chalcolithic period in the Near East (c. 6000-3500 BC). However, previous studies on pyrotechnological installations, such as pottery kilns, pertaining to this period, have often been mainly descriptive, with a limited use of archaeometric investigations. This work presents a multi-method investigation of a Chalcolithic kiln recently discovered in the Bora Plain (part of the larger Peshdar Plain, in Iraqi Kurdistan), which combines stratigraphic analysis, pyrotechnological, micromorphological, and micro-remains analyses. Since this kiln represents the first Chalcolithic architectural feature excavated in the Bora Plain, this work offers precious insights into the pyrotechnology of the period, which is still relatively poorly understood, through the reconstruction of the kiln’s use and abandonment processes. The analytical outputs can be used to compare with other Near East kilns from the Chalcolithic and later periods.
Gesehen am 16.10.2023